We Are Going to Be Pals! - Teague, Mark (New York : Beach Lane Books, an imprint of Simon & Schuster Children's Publishing Division, 2023)
A talkative cattle egret explains to a rhinoceros that in addition to having a symbiotic relationship, they also have a friendship built on communication, kindness, and a respect for boundaries.
Keywords: Cattle egret -- Juvenile fiction; Rhinoceroses -- Juvenile fiction; Symbiosis -- Juvenile fiction; Friendship -- Juvenile fiction; Rhinoceroses -- Fiction; Cattle egrets -- Fiction; Heron family (Birds) -- Fiction; Symbiosis -- Fiction; Friendship -- Fiction; Animal fiction; Picture books